SOURCES ON CHANGES IN THE CULTURE OF EVERYDAY LIFE OF THE NOMADIC POPULATION OF CENTRAL ASIA (Neo Scientific Peer Reviewed Journal, 2023)
Issues of the history of the nomadic population of Central Asia are one of the problematic areas of source study. Many historians, travelers and diplomats wrote about the economic life, scientific life and culture of the nomadic population. In the given article the documents of Turkestan’s Governor’s Office kept in the funds of the Central Archives of the Republic of Uzbekistan are considered as the sources of investigations and give a chance to make up some conclusions concerning the life of nomadic people of Central Asia.